2007
DOI: 10.1063/1.2825070
|View full text |Cite
|
Sign up to set email alerts
|

Geodetic laser scanning

Abstract: Producing surface maps at submeter resolution, even over heavily forested terrain, GLS can reveal the fine structure of such features as faults, landslides, and drainage patterns.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(38 citation statements)
references
References 6 publications
1
37
0
Order By: Relevance
“…2. This shows a recent Physics Today cover graphic of a new geospatial laser mapping technology that can penetrate tree cover (Carter, Shrestha, & Slatton, 2007). The authors themselves were surprised that the resulting visual representation revealed more underlying topography by showing less information.…”
Section: Increasing Spatial Reproduction Fidelitymentioning
confidence: 99%
“…2. This shows a recent Physics Today cover graphic of a new geospatial laser mapping technology that can penetrate tree cover (Carter, Shrestha, & Slatton, 2007). The authors themselves were surprised that the resulting visual representation revealed more underlying topography by showing less information.…”
Section: Increasing Spatial Reproduction Fidelitymentioning
confidence: 99%
“…The Airborne Laser scanner System is an active remote sensing sensor, that coupled laser fastened on an aircraft with precise kinematic positioning provided by a differential global positioning system (DGPS) to produce accurate elevation measurements (Carter, 2007). Acquisition data from Potenza city is formulated by a "Topeye MKII" system .…”
Section: Data Collection and Processingmentioning
confidence: 99%
“…These show gross topography for regions situated below 2000 m a.s.l., with a vertical accuracy and of about 50 cm and a density of points of 1 m 2 (Carter et al, 2007;Schulz, 2007;SWISSTOPO, 2007). Several standard ArcGIS tools using DEMs are useful for geomorphological interpretation.…”
Section: Digital Elevation Models and Arcgis Toolsmentioning
confidence: 99%